2004
DOI: 10.1196/annals.1293.005
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Reactive Oxygen Species Generation and Calcium Increase Induced by Visible Light in Astrocytes

Abstract: Mitochondria contain photosensitive chromophores that can be activated or inhibited by light in the visible range. Rather than utilizing light energy, however, mitochondrial electron transport oxidation-reduction reaction and energy coupling could be stimulated or damaged by visible light. Our previous work demonstrated that reactive oxygen species (ROS) were generated in cultured astrocytes after visible laser irradiation. With confocal fluorescence microscopy, we found that ROS were generated mostly from mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 18 publications
2
31
1
Order By: Relevance
“…In the current study, we found that mROS generation is prior to mCa 2+ increase in control and ρ 0 astrocytes after H 2 O 2 treatment. These findings were compatible with our previous studies on H 2 O 2 [32] and photoirradiation-augmented oxidative stress [3335]. Moreover, our study provided quantitative imaging evidence that dual effect on antioxidation exists in ρ 0 astrocytes during different extent of oxidative stress.…”
Section: Discussionsupporting
confidence: 93%
“…In the current study, we found that mROS generation is prior to mCa 2+ increase in control and ρ 0 astrocytes after H 2 O 2 treatment. These findings were compatible with our previous studies on H 2 O 2 [32] and photoirradiation-augmented oxidative stress [3335]. Moreover, our study provided quantitative imaging evidence that dual effect on antioxidation exists in ρ 0 astrocytes during different extent of oxidative stress.…”
Section: Discussionsupporting
confidence: 93%
“…Several mechanisms explaining ROS generation have been suggested in mitochondria, which are associated with mitochondrial membrane potential, nitric oxide, and Ca 2+ influx. 31,32) Recently, Sun et al suggested that NADPH oxidase activation is an initiator of mitochondrial damage, which eventually results in the death of HepG2 cells. 33) Based on these results, we also measured the enzyme activity after treatment with cationic NPs used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescence laser scanning is known to induce reactive oxygen species (Jou et al, 2004), which may induce the release of free zinc from zinc-binding proteins such as metallothionein, independent of receptor-mediated signaling events. To identify the subcellular regions where the zinc wave originates while avoiding secondary effects caused by cell stress, we used a thin-layer illumination microscope system that was based on the total internal reflection fluorescence (TIRF) microscope (Tokunaga et al, 1997).…”
Section: Resultsmentioning
confidence: 99%